Ответ:
[tex]1) \frac{45}{11} \\ 2) x = \frac{39}{50} [/tex]
Пошаговое объяснение:
[tex]1)5 - ( \frac{4}{11} + \frac{6}{11} ) = 5 - \frac{10}{11} = \frac{45}{11} [/tex]
[tex]2) \frac{15}{50} - (1 - x) = \frac{4}{50} = \frac{15}{50} - 1 + x = \frac{4}{50} = \frac{15}{50} - 1 + x = \frac{2}{25} = - \frac{7}{10} + x = \frac{2}{25} = x = \frac{2}{25} + \frac{7}{10} = x = \frac{39}{50} [/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]1) \frac{45}{11} \\ 2) x = \frac{39}{50} [/tex]
Пошаговое объяснение:
[tex]1)5 - ( \frac{4}{11} + \frac{6}{11} ) = 5 - \frac{10}{11} = \frac{45}{11} [/tex]
[tex]2) \frac{15}{50} - (1 - x) = \frac{4}{50} = \frac{15}{50} - 1 + x = \frac{4}{50} = \frac{15}{50} - 1 + x = \frac{2}{25} = - \frac{7}{10} + x = \frac{2}{25} = x = \frac{2}{25} + \frac{7}{10} = x = \frac{39}{50} [/tex]